A model reconstruction of Antarctic sea-ice thickness and volume changes over the past decades using data assimilation - Massonnet, François; Mathiot, Pierre; Fichefet, Thierry; Goosse, Hugues; Vancoppenolle, Martin; König Beatty, Christof; Lavergne, Thomas; In Proceedings of the International Symposium on Sea Ice in a Changing Environment (2014)
Sea-ice variability in the Southern Ocean has a complex spatio–temporal structure. In a global warming context, the Antarctic sea-ice cover has slightly expanded over the recent decades. This increase in sea-ice extent results, however, from the sum of positive and negative regional trends and is influenced by a wide range of modes of climate variability. An additional view on sea-ice thickness and volume changes would improve our understanding. Still, no large-scale multi-decadal well-sampled record of Antarctic sea-ice thickness exists to date. To address this issue, we assimilate real sea-ice concentration data into the ocean–sea-ice model NEMO-LIM2 using an ensemble Kalman filter, and demonstrate the positive impacts on the global sea-ice cover. We find that the global Antarctic sea-ice volume has risen at a significant pace over the period 1980–2008, with an increase in the Ross and Weddell Seas and a decrease in the Amundsen-Bellingshausen Seas. Sea-ice volume anomalies co-vary well with extent anomalies, and exhibit yearly to decadal fluctuations. The results stress the need to analyze sea-ice changes at the regional level first and then at the hemispheric level.